The Informal Labour Market in India: Transitory or Permanent Employment for Migrants? - Pramod N. (Raja) Junankar; Abu Shonchoy (Institute for the Study of Labor (IZA), 2013)
This paper studies the characteristics of the workers in the informal economy and whether migrants treat this sector as a temporary location before moving on to the organised or formal sector to improve their life time income and life style. We limit our study to the Indian urban (non-Agricultural) sector and study the characteristics of the household heads that belong to the Informal Sector (Self Employed and Informal Wage Workers) and the Formal Sector. We find that household heads that are less educated, come from the poorer households, lower social groups (castes and religions) are more likely to be in the informal sector. We distinguish between migrants who come from rural areas and urban areas to their present urban location. We find that the longer duration of a rural migrant in the urban area, the lower the probability that the household head would be in the informal wage labour sector.
Keywords: O17; J15; J61; J42; 330; informal labour markets; migrant; caste; religion